Latar Belakang Masalah dan Konflik Batin Para Pelaku Jouhatsu di Jepang ditinjau dalam Konteks Penerjemahan - Maria Angelina; Althaf Gauhar Auliawan (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2025)
This study aims to find out how the background and inner conflict experienced by jouhatsu actors in Japan are viewed in the context of translation so that Indonesian readers can understand and capture the hidden meaning of the phenomenon. This research uses Newmark's theory of modulation and Venuti's theory of foreignization. The research method used is qualitative research with case studies. The subjects of this research are jouhatsu actors in Japan who were interviewed by the South China Morning Post's youtube channel entitled “Japan's ‘evaporated’ people: Inside an industry that helps people disappear” and CNA titled ‘Vanishing without a trace | Undercover Asia as well as a book titled ’The Vanished: The 'Evaporated People' of Japan in Stories and Photographs.” by Mauger and Remael. This study found that 24 data analyzed by the author in the context of translation were translated using modulation technique and 12 data were translated using footnote technique. The data shows that Newmark's modulation technique is able to translate well the implied meaning hidden in the speaker's statement. Venuti's foreignization strategy is used to analyze the research data from a cultural perspective so that the jouhatsu phenomenon can be well understood by people outside Japan. Footnotes are used to translate words that do not exist in Indonesian. With the techniques of modulation, foreignization, and footnotes, translation becomes not only a process of language transfer, but also a transfer of culture and emotion. Indonesian readers do not just know that someone “disappeared”, but also understand the economic background, social pressure, violence, fear, shame, and regret that drove someone to become a jouhatsu-sha.